Efficacy of oral sarolaner for the treatment of generalized demodicosis in dogs - Goulart Carvalho, Flavia Clare; Lopes, Natália Lôres; Machado, Marília Alves; Merlo, Alexandre; Fernandes, Julio Israel (Brazilian Journal of Veterinary Medicine, 2019)
The aim of this study was to report the treatment efficacy of generalized demodicosis with oral sarolaner in dogs. Twenty-seven dogs diagnosed with generalized demodicosis were treated with oral sarolanerat a dose of 2.0 mg/kg every 30 days. Sarolaner was administered on days 0, 30, 60, and 90. The dogs were analyzed as positive or negative for demodicosis. Clinical parameters were recorded before and after treatment every 30 days for 90 days. On day 30, 77.7% of the dogs exhibited negative results for demodicosis in skin scrapings, and on day +60, 100% of dogs showed negative results on parasitological examination, which continued until day 90. On day 30, 7.41% of the dogs showed clinical remission, followed by 74.07% on day +60. On day +90, 88.88% of the dogs showed complete clinical recovery. Sarolaner was effective in treating canine generalized demodicosis and could be an excellent alternative to conventional treatment, especially for animals in whom ivermectin is contraindicated.